When birds are near dispatches from contemporary writers - Rogers, Susan Fox (Comstock Publishing Associates, an imprint of Cornell University Press, 2020)
"This book is a literary collection that explores and celebrates a life with birds"--
Description based on print version record
Keywords: Birds -- Literary collections; Bird watching -- Literary collections; Essays